Still curling after all these years: Glenodinium apiculatum Ehrenb. (Peridiniales, Dinophyceae) repeatedly found at its type locality in Berlin (Germany). Issue 2 (17th February 2018) - Kretschmann, Juliane; Čalasan, AnŽe Žerdoner; Kusber, Wolf-Henning; Gottschling, Marc
Abstract : The contemporary occurrence of dinophytes at their type localities has not been intensely studied so far, despite the type locality's crucial importance for any reliable scientific name application. The microscopist and phycologist Ch.G. Ehrenberg described a number of dinophyte species more than 150 years ago, many of which are currently taxonomically ambiguous. We collected water tow and sediment samples at those same localities in Berlin that Ch.G. Ehrenberg may have visited as well. We isolated and established several strains of Glenodinium apiculatum that we investigated by applying contemporary microscopic and molecular methods. The plate formula of the species was 4′, 2a, 7″, 6c, 5s, 5′″, 2″″, without an apical pore complex, and the most distinctive morphological trait of Glenodinium apiculatum was the spiny hypotheca. The spines were irregularly scattered over hypothecal plate surface and arranged in raised edges between thecal plates. As inferred from molecular phylogenetics, Glenodinium apiculatum is assigned to Palatinus, which is an element of the Peridiniopsidaceae as a part of the Peridiniales. For taxonomic purposes, we epitypified Ch.G. Ehrenberg's taxon with newly collected material to ensure a reliable determination in the future. Palatinus apiculatus is not a fleeting star, and a number of dinophytes show a remarkably high fidelity to the sites from which they were originally described, even if the description was carried out a long time ago.